Pharmacokinetics and Bioequivalence of Two Formulations of Valsartan 80 mg Capsules: A Randomized, Single Dose, 4-Period Crossover Study in Healthy Chinese Volunteers Under Fasting and Fed Conditions - Wu Q; Wang X; Chen Q; Zou Y; Xu X; Li T; Yu C; Zhu F; Zhang KE; Jia J; Liu Y (Dove Medical Press, 2020)
Qingqing Wu,1,2 Xiaodong Wang,3 Qian Chen,1,2 Yang Zou,1,2 Xiaoyan Xu,1,2 Tingting Li,1,2 Chen Yu,1,2 Fu Zhu,1,2 Kanyin E Zhang,4 Jingying Jia,1,2 Yanmei Liu1,2 1Center Laboratory, Shanghai Xuhui Central Hospital, Shanghai, People’s Republic of China; 2Shanghai Engineering Research Center of Phase I Clinical Research & Quality Consistency Evaluation for Drugs, Shanghai, People’s Republic of China; 3Changzhou Siyao Pharmaceuticals Co., Ltd, Jiangsu, People’s Republic of China; 4ViaClinical Ltd, Shanghai, People’s Republic of ChinaCorrespondence: Yanmei LiuCenter Laboratory, Shanghai Xuhui Central Hospital, No. 966, Huaihai Road(M), Shanghai, People’s Republic of ChinaTel/Fax +86-21-54030254Email ymliu@shxh-centerlab.comPurpose: To compare the bioequivalence of two formulations of valsartan (80 mg capsules) under fasting and fed conditions in healthy Chinese volunteers using a full-replicate study design.Methods: A total of 78 Subjects were randomly assigned to fasting cohort (n = 48) or fed cohort (n = 30). Each cohort includes 4 single-dose observation periods and 3-day washout periods. Blood samples were collected at designed time point. Plasma concentration of valsartan was analyzed by a validated LC-MS/MS method. Noncompartmental analysis method was employed to determine the pharmacokinetic parameters. Based on the within-subject standard deviation (SWR) of the reference formulation, either reference-scaled average bioequivalence (RSABE) or average bioequivalence (ABE) method was used to evaluate the bioequivalence of the two formulations.Results: Under fasting conditions, the RSABE method was used to evaluate the bioequivalence of Cmax (SWR> 0.294), while ABE method was used to evaluate the bioequivalence of AUC0-t and AUC0-∞. The geometric mean ratio (GMR) of the test/reference for Cmax was 99.52%, and the 95% upper confidence bound was < 0. For AUC0-t and AUC0-∞ comparisons, GMRs were 102.07% and 101.92%, and the 90% CIs of the test/reference were 96.28%– 108.21%, 96.28%– 107.88%, respectively. Under fed conditions, the SWR value of Cmax, AUC0-t and AUC0-∞ all exceeded the cutoff value of 0.294 and therefore, the RSABE method was used. The GMRs for Cmax, AUC0-t and AUC0-∞ were 98.78%, 103.33% and 103.08%, respectively, while the 95% upper confidence bound values were all < 0. These results all met the bioequivalence criteria for highly variable drugs. All adverse events were mild and transient.Conclusion: In this study, the generic formulation of valsartan 80 mg capsule was considered to be bioequivalent to the reference product under both fasting and fed conditions, and satisfied the requirements for marketing in China.NMPA Registration No: CTR20181422.Keywords: valsartan, bioequivalence, replicate, pharmacokinetics, safety